2014
DOI: 10.1155/2014/649502
|View full text |Cite|
|
Sign up to set email alerts
|

Thyrotoxic Periodic Paralysis: Clinical Challenges

Abstract: Thyrotoxic periodic paralysis (TPP), a disorder most commonly seen in Asian men, is characterized by abrupt onset of hypokalemia and paralysis. The condition primarily affects the lower extremities and is secondary to thyrotoxicosis. The underlying hyperthyroidism is often subtle causing difficulty in early diagnosis. Factors like high-carbohydrate meal exercise, steroid, and stress can precipitate an attack of TPP. Evidence is building up showing role of genetic mutations in Kir2.6 channel in the pathogenesis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
167
0
12

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 77 publications
(182 citation statements)
references
References 48 publications
3
167
0
12
Order By: Relevance
“…Depending on the general condition of the patient , potassium supplementation is given either orally or intravenously. 2 One prospective study compared treatment with intravenous potassium chloride to normal saline infusion and found a shorter recovery time with use of potassium (6.3 v/s. 13.5 hours Non-selective beta blockers like propranolol can be given at the time of acute attacks and also to prevent recurrence.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Depending on the general condition of the patient , potassium supplementation is given either orally or intravenously. 2 One prospective study compared treatment with intravenous potassium chloride to normal saline infusion and found a shorter recovery time with use of potassium (6.3 v/s. 13.5 hours Non-selective beta blockers like propranolol can be given at the time of acute attacks and also to prevent recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…Acetazolamide, which has been reported to decrease the frequency of paralytic attacks in FHPP, should never be given to patients with TPP as it may actually worsen the attack. 2 Although glucocorticoids have been used to treat hyperthyroidism, they may also produce detrimental effects, including the development of TPP. A literature review revealed at least 2 cases of TPP induced by methylprednisolone and 2 cases caused by a single dose of prednisone.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations